Penggunaan Ekstrak Daun Gamal (Gliricidia sepium Jacq.) dan Beauveria bassiana (Bals.) VuillLokal untuk Mengendalikan Hama Spodoptera litura F. di Laboratorium - Putri, Ulfa Nabila; Salbiah, Desita; Fauzana, Hafiz (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Spodoptera litura is main pest that attack corn plant. The farmers still using chemical insecticide to control S. litura so needed other safe and environment friendly methods. Effective and environment friendly control methods can use gamal leaf as botanical insecticide and entomopathogenic fungi local B. bassiana. The research was to knows interaction of gamal leaf extract (Gliricidia sepium) with entomopathogenic fungi local B. bassiana to control army worm pest (Spodoptera litura) to corn plant. The research uses Factorial Random Design (RAL) consisting of 2 factors. The first factor is concentration of gamal leaf extract consisting of 4 levels is  gamal leaf extract 0 g.l-1of water, gamal leaf extract 3 g.l-1of water, gamal leaf extract 6 g.l-1of water, and gamal leaf extract 9 g.l-1of water. The second factors is concentration of entomopathogenic fungi local Beauveria bassiana consisting of 4 levels is B. bassiana 0 g.l-1of water,                B. bassiana 25 g.l-1 of water, B. bassiana 30 g.l-1 of water, and B. bassiana 35 g.l-1 of water. The data obtained were analyzed statistically with variance and continued with Duncan’s New Multiple Range Test (DNMRT) at 5%.  The results showed that the interaction between gamal leaf extract and entomopathogenic fungi local Beauveria bassiana. Keywords : gamal leaf extract, local Beauveria bassiana, Spodoptera litura